Faktor-Faktor yang Berhubungan dengan Diabetes Self Care Management pada Pasien Diabetes Mellitus Tipe 2 - Alfatikhatu Khoirun Nisak; Suyanto Suyanto; Indah Sri Wahyuningsih (Stikes Kesdam IV/Diponegoro Semarang, Indonesia, 2025)
Complication rates among patients with Type 2 DM are increasing and worsening due to their inability to implement self-care management. However, this cause can be minimized if patients have good knowledge, self-efficacy, and family support. The study used a quantitative approach with a cross-sectional design. The sample consisted of 147 respondents with type 2 diabetes in Bandarharjo Community Health Center Semarang, who were selected using purposive sampling technique. The test used was chi square test. The study showed that most respondents had low knowledge (47.6%), poor self efficacy (44.2%), adequate family support (49.7%) and good self care management (46.3%). The results showed a relationship between knowledge, self efficacy and family support on self care management in Type 2 DM patients at Bandarharjo Semarang Health Center (p<?). The results showed that there is a relationship between knowledge, self efficacy and family support on self care management in patients with Type 2 DM at Bandarharjo Community Health Center Semarang.